Irrigation requirement in gram (Cicer arietinum) + Indian mustard (Brassica jancea) intercropping system - Ahlawat, IPS; Gangajah, B; Singh, Ompal (The Indian Journal of Agricultural Sciences, 2005)
A field experiment was conducted during 2000-2002 at the Indian Agricultural Research Institute, New Delhi, to find out the optimum irrigation schedule for gram (Cicer arietimum L.) + Indian mustard [Brassica juncea (L.) Czernj. & Cosson] intercropping system. Irrigation at 0.2 irrigation water : cumulative pan evaporation (IW : CPE) ratio in sole gram and 0.4 IW : CPE ratio in Indian mustard was optimum for seed yield. Irrigation in gram at 0.4IW : CPE ratio caused 31.6% reduction in seed yield compared with 0.2 IW : CPE ratio. The yield of gram + Indian mustard in intercropping systems was dependent on row proportions of coinponent crops. Gram-equivalent yield (GEY) was the highest in sole Indian mustard (3.04 tonnes/ha) and with irrigation at 0.2 IW : CPE ratio (2.42 tonnes/ha). At closer row proportions (2:1 and 3:1) of gram and Indian mustard intercropping system, irrigation at 0.4 IW : CPE ratio recorded higher gram-equivalent yield (2.88, 2.744 tonnes/ha), while at wider row proportions (4:1 and 6:1) irrigation at 0.2 IW : CPE ratio gave higher gram-equivalent yield (2.41 and 2.33 tonnes/ha). The water-use efficiency (kg/ha-mm) was the highest in sole Indian mustard (12.66) and unirrigated crops (11.7).